IMPACT OF RECRUITMENT ON THE ORGANIZATION AND ORGANIZATIONAL DESIGN - Sharma, Mohit (Digital Repository of Theses, 2023)
The introduction of the thesis paper sets the context for the topic by highlighting the importance of recruitment in organizational strategy and introducing the research questions that the paper aims to answer. The introduction also outlines the structure of the paper, providing a brief overview of the key sections and their contents. The literature review section of the paper provides a comprehensive overview of the existing research on the impact of recruitment on the organization and organizational design. This section covers a range of topics, including the quality of the workforce, the culture of the organization, the dynamics of organizational design, diversity and inclusion in recruitment, and the role of leadership in shaping effective recruitment strategies. The literature review section synthesizes and analyzes the existing research, identifying key themes and insights. The methodology section of the thesis paper explains the research methods and data sources used to investigate the research questions. This section describes the research design, data collection methods, and data analysis techniques used to generate the findings of the paper. The methodology section also includes a discussion of the limitations of the research and strategies used to address them. The findings section of the thesis paper presents the results of the research, organized according to the research questions. This section provides a detailed analysis of the impact of recruitment on the organization and organizational design, drawing on the literature review and data analysis. The findings section also identifies best practices and recommendations for optimizing recruitment practices to achieve long-term success. The conclusion of the thesis paper summarizes the key findings and their implications for organizational strategy and recruitment practices. The conclusion also discusses the limitations of the research and provides suggestions for future research on the topic. Overall, the thesis paper provides a comprehensive analysis of the impact of recruitment on the organization and organizational design, drawing on existing research and case studies. The paper offers insights into the importance of effective recruitment practices and their role in shaping the success and sustainability of a business. The paper's recommendations can be used by organizations to optimize their recruitment practices and achieve long-term success. Recruitment and selection are the two phases of the employment process, but there is a difference between them. The first is the process of searching the candidates to fill identifies vacant and stimulating them to apply for jobs in the organization, while the later involves a series of steps by which the candidates are screened to choose the most suitable persons for vacant positions. (Ph.D et al., 2017) The purpose of this research begins from here. This research is focused on discussing various factors making an impact on an organization’s design. The most critical aspect for any organization is its human capital, and the impact it can create on an organizational design and internal dynamics is the primary focus of this dissertation. The method used is a research questionnaire from 100+ HR professionals from Banking Industry and establish the basis by evaluating the response to the questionnaire.